1977
DOI: 10.1152/ajpheart.1977.233.4.h466
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic flow through the placental barrier of chronically prepared sheep

Abstract: An electromagnetic flow sensor was placed on the distal aorta of sheep fetuses in utero, and catheters were placed in a femoral artery and the common umbilical vein. Catheters were also placed in a carotid artery and a uterine vein of the pregnant ewe. Three days postoperatively maternal plasma was hyperosmotic with respect to fetal plasma by all methods: +5.8 +/- 1.4 SE by vapor-pressure osmometry, +2.2 +/- 0.7 SE by freezing-point depression osmometry corrected for bicarbonate loss; and +3.26 mosmol/liter by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Fetal plasma AVP levels did not change in response to the under aerobic conditions (10). More precise determinations un-intraamniotic rehydration.…”
Section: Fetal Rehydration (Intraamniotic)mentioning
confidence: 81%
See 1 more Smart Citation
“…Fetal plasma AVP levels did not change in response to the under aerobic conditions (10). More precise determinations un-intraamniotic rehydration.…”
Section: Fetal Rehydration (Intraamniotic)mentioning
confidence: 81%
“…der anaerobic conditions, which reduce plasma carbon diox-rehydration resulted in decreased fetal plasma osmolality but a ide loss, indicate actual plasma osmolality gradients of 2 to 3 continued elevation of plasma AVP (5). As dehydration-induced mosmol/kg (10). Despite ad libitum feeding, postprandial fetal blood volume contraction was not normalized by maternal changes in maternal plasma osmolality (1 1) also may have con-rehydration in the prior study, it suggested that AVP secretion tributed to the observed basal osmotic gradient.…”
Section: Fetal Rehydration (Intraamniotic)mentioning
confidence: 96%
“…Arterial blood gases were measured using an IL pHblood gas analyzer (micro 13, Instrumentation Laboratory, Lexington, MA) or a CIBA-Corning blood gas system (model 288, Medfield, MA). Plasma bicarbonate concentration was calculated using a modified Henderson-Hasselbach equation (10). Hematocrit was measured in duplicate using a hematocrit centrifuge and reader.…”
Section: Methodsmentioning
confidence: 99%
“…GFR was calculated as the renal clearance of 125 I-labeled sodium iothalamate, and fractional reabsorption of sodium by the proximal and distal nephron was calculated from the renal clearance of lithium (22). Plasma bicarbonate concentrations were calculated using a formula derived from the Henderson-Hasselbach equation (1). Filtration fraction relative to control was calculated from the formula, Filtration fraction ϭ GFR c/RBFc, where GFRc and RBFc are expressed as a percentage of their respective control values.…”
Section: Methodsmentioning
confidence: 99%